Comparison of Body Perception of Bodybuilding Athletes pre and post Anabolic Steroid Cycle - Bulgurcuoglu, Ahmet Nusret; Tazegul, Unsal (Progress in Nutrition, 2021)
Study Objectives: This study aimed to compare the body perception levels of elite bodybuilders’ pre and post steroid cycles. Methods: The experimental group consisted of 42 steroid-using bodybuilders who voluntarily agreed to participate in the study. Besides, the control group was formed by 22 people. Athletes in the control group did not use steroids. As a data collection tool, the Body Appreciation Scale was used. Two-way repeated measure analysis of variance, frequency analysis, and descriptive statistical analysis were used in the analysis of the data. Results: According to the statistical analysis results, it was determined that there was an increase in body discontent levels of athletes after steroid cure. Conclusion: It was revealed that the use of steroids increased the level of body discontent of athletes. To be healthier, it is better to have an active lifestyle (adequate exercise), healthy eating habits, and maintain a positive state of mind.